Brexit and European Finance: Prolonged Limbo - Nicolas Véron (CESifo Forum, 2021)
Following the orderly British exit from the European single market in late 2020, the full impact of Brexit on the financial sector has been delayed by risk aversion in the public and private sector alike, in part related to the Covid-19 pandemic. It will take longer than many had anticipated for the dust to settle on the post-Brexit financial landscape and its respective implications for the EU and the UK.
Keywords: 330